Factors Affecting Student Satisfaction in Distance Learning: A Case Study of COMSATS (VIRTUAL CAMPUS) - Muhammad Rizwan (Universitas Negeri Padang, 2021)
Generally, In Pakistan people perceived that quality of distance learning education is poor. Therefore, we decided to carry out the study to see if it’s only people opinion or legend. The aim of the study is to analyze the association between instructor performance (IP), student instructor interaction (SII), course evaluation (CE) and student satisfaction (SS) variables in distance education by taking Virtual COMSATS as a Case study. Target population of this research was the COMSATS (VIRTUAL CAMPUS). students out of which 251 graduate and undergraduate students were selected as sample for current research. The purpose of this research study was to understand the key factors affecting student satisfaction in distance learning .Researchers also collect information through primary data using survey questionnaire that distributed through email to all the students of VCOMSAT. From literature review it was found that in distance learning education student satisfaction is based on instructor performance, student-instructor interaction, course evaluation, Learning management system use, instructor attitude etc. From literature review we found that course evaluation and instructor performance is very important for student satisfaction in distance learning. Researchers need to compare student’s satisfactions with subject wise. Comparison of practical subjects and without practical subjects needs to identify with student satisfaction. There is also required to compare lecturer motivation with student satisfaction and performance. Future research is also need to compare satisfaction of rural area and urban areas students in distance learning education and also need to compare with traditional education.